Nuclear pore complexes and nucleocytoplasmic transport: methods - Doye, Valérie (Methods in cell biology, 2014)
Front Cover; Nuclear Pore Complexes and Nucleocytoplasmic Transport -- Methods; Copyright; Contents; Contributors; Preface; Chapter 1: Fifty Years of Nuclear Pores and Nucleocytoplasmic Transport Studies: Multiple Tools Revealing Complex Rules; Introduction; 1.1. The NPCs: A Modular Macromolecular Assembly; 1.1.1. Toward a refined view of the NPC structure; 1.1.2. Nucleoporins: The building blocks of NPCs; 1.1.3. Integrating the Nups into the 3D architecture of the NPC; 1.1.3.1. Nup localization; 1.1.3.2. Interactions among Nups; 1.1.3.3. Nup stoichiometry